Conceptualizing resilience in adult mental health literature: A systematic review and narrative synthesis. (11th June 2018) - Ayed, Nadia; Toner, Sarah; Priebe, Stefan
Abstract : Purpose: This review aims to identify how the term 'resilience' is conceptualized across adult mental health research due to ongoing criticism regarding the lack of consistency in its conceptualization. Method: A systematic search, including hand searches of book chapters, was conducted using search terms ('resilien*') AND ('mental illness' OR 'mental health problem'). Papers were excluded if they did not meet the following criteria: written in English, provide a clear conceptualization of resilience, include only adults (aged 18 + ) in the sample, solely focus on individuals with a primary diagnosis of mental illness, and peer‐reviewed. Data were extracted on conceptualizations of resilience, demographic, and diagnostic variables of the study population, publication year, and the research design used. Conceptualizations were combined and collapsed into overarching themes and then refined through joint discussion, consultation with a third reviewer, and input from a larger multidisciplinary team. Results: Thirty‐one texts (6 book chapters, 4 reviews, 2 appraisals/critical evaluations, 1 editorial, and 18 research projects) were included. Two broad understandings of resilience were identified: resilience as a process and resilience as a characteristic of an individual. Processes comprise three themes: 'immunity', 'bouncing back', and 'growth', whilst characteristics are captured in two themes 'personal resources' and 'social resources'. Conclusions: These findings suggest that resilience can be conceptualized in a clear and meaningful manner in adult mental health research. The five themes reflect distinct ways of using the term resilience. Whilst each one of them may have merit in future research, it appears beneficial to make clear in research which exact conceptualization of resilience has been adopted. Practitioner Points: When considering and reading about 'resilience', one should be aware that there are different concepts of it. The main difference is between resilience as a personal characteristic and resilience as a process. Therapy may address resilience as a personal characteristic by utilizing individual and social resources. The therapeutic process may be understood as resilience in form of bouncing back and personal growth.